Development of a real‐time patient‐reported outcome measure for symptom assessment in patients with functional dyspepsia using the experience sampling method. Issue 2 (4th November 2018) - Smeets, Fabiënne G. M.; Keszthelyi, Daniel; Vork, Lisa; Tack, Jan; Talley, Nicholas J.; Simren, Magnus; Aziz, Qasim; Ford, Alexander C.; Conchillo, José M.; Kruimel, Joanna W.; Van Os, Jim; Masclee, Ad A. M.
Abstract: Background: Patient‐reported outcome measures (PROMs) are used to assess symptoms in patients with functional dyspepsia (FD). Current end‐of‐day questionnaires have several limitations including sensitivity to recall and ecological bias. The experience sampling method (ESM) is characterized by random and repeated assessments across momentary states in daily life and therefore less sensitive to these limitations. This study describes the development of a novel PROM based on ESM technology. Methods: An initial draft of the PROM was developed based on literature. Focus group interviews with FD patients according to Rome IV criteria, and an expert meeting with international opinion leaders in the field of functional gastrointestinal disorders were conducted in order to select items for the PROM. Cognitive interviews were performed to evaluate patients' understanding of the selected items and to create the definitive PROM. Key results: A systematic literature search revealed 59 items across four domains (ie, physical status; mood and psychological factors; context and environment; and nutrition, medication, and substance use). After patient focus group interviews and an international expert meeting, the number of items was reduced to 33. Cognitive interviews resulted in some minor linguistic changes in order to improve patients' understanding. Conclusions and inferences: A novel digital ESM‐based PROM for real‐time symptom assessment in patients with functional dyspepsia was developed. This novel PROM has the potential to identify individual symptom patterns and specific triggers for dyspeptic symptoms, and optimize treatment strategies. Abstract : A digital disease‐specific patient‐reported outcome measure (PROM) for real‐time symptom assessment in patients with functional dyspepsia was developed. We suggest that the newly developed ESM‐based PROM might be able to assess dyspeptic symptoms, identify specific triggers for symptoms, optimize (individualized) treatment strategies, and could potentially be used as an instrument to quantify therapeutic efficacy.